A case of paraparesis due to extramedullary haemopoiesis in HbE-thalassaemia. Issue 621 (July 1977) - Mihindukulasuriya, J. C.; Chanmugam, D.; Machado, V.; Samarasinghe, C. A.
Abstract : A 24-year-old female with haemoglobin E-thalassaemia who presented with paraparesis of 18 months' duration was found to have spinal extradural extramedullary haemopoietic tissue extending from T4 to T9. Complete neurological recovery followed laminectomy. The importance of prompt diagnosis and treatment, of this unusual complication of extramedullary haemopoiesis, before the spinal cord is irreversibly damaged is stressed.